Deformation of crystalline materials part 1 (Strength and Deformation of Solids, 1975)
This video present a fifty-foot copper wire which is deformed under different loads. The components of elastic, anelastic, and plastic deformation are plotted on a stress-strain diagram. Uses split-screen presentation of the observed deformation and the stress-strain curves to emphasize their interpretation. From the Strength and Deformation of Solids series.